PENGARUH HARGA, PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIANG ULANG TEH DAUN GAMBIR SONDEL DI KABUPATEN PAKPAK BHARAT - Munte, Astoti; Daulay, Akman; Umi Kalsum, Eka (Fakultas Ekonomi Universitas Al-Azhar Medan, 2024)
The purpose of this study was to determine the influence of price, promotion and product quality on repurchase decision of Teh Daun Gambir Sondel in Pakpak Bharat Regency. The population of this study consisted of people from Pakpak Bharat Regency who were regular purchasers of Teh Daun Gambir Sondel. The sample used consisted of 97 respondents. The sampling technique used was purposive sampling. The research data was collected using quantitative methods using a questionnaire whose validity, reliability, assumptions and classical hypotheses were tested using data analysis techniques using multiple linear regression analysis.The results of this study partially show that price, advertising and product quality have a positive and significant influence on purchasing decisions. At the same time, price, promotion and product quality simultaneously have a positive and significant impact on the repurchase decisions of Teh Daun Gambir Sondel in Pakpak Bharat Regency